Disrupted Iron Storage in Dental Fluorosis. (August 2019) - Houari, S.; Picard, E.; Wurtz, T.; Vennat, E.; Roubier, N.; Wu, T.D.; Guerquin-Kern, J.L.; Duttine, M.; Thuy, T.T.; Berdal, A.; Babajko, S.
Enamel formation and quality are dependent on environmental conditions, including exposure to fluoride, which is a widespread natural element. Fluoride is routinely used to prevent caries. However, when absorbed in excess, fluoride may also lead to altered enamel structural properties associated with enamel gene expression modulations. As iron plays a determinant role in enamel quality, the aim of our study was to evaluate the iron metabolism in dental epithelial cells and forming enamel of mice exposed to fluoride, as well as its putative relation with enamel mechanical properties. Iron storage was investigated in dental epithelial cells with Perl's blue staining and secondary ion mass spectrometry imaging. Iron was mainly stored by maturation-stage ameloblasts involved in terminal enamel mineralization. Iron storage was drastically reduced by fluoride. Among the proteins involved in iron metabolism, ferritin heavy chain (Fth), in charge of iron storage, appeared as the preferential target of fluoride according to quantitative real-time polymerase chain reaction, Western blotting, and immunohistochemistry analyses. Fluorotic enamel presented a decreased quantity of iron oxides attested by electron spin resonance technique, altered mechanical properties measured by nanoindentation, and ultrastructural defects analyzed by scanning electron microscopy and energy dispersive x-ray spectroscopy. The in vivo functional role of Fth was illustrated with Fth +/- mice, which incorporated less iron into their dental epithelium and exhibited poor enamel quality. These data demonstrate that exposure to excessive fluoride decreases ameloblast iron storage, which contributes to the defective structural and mechanical properties in rodent fluorotic enamel. They raise the question of fluoride's effects on iron storage in other cells and organs that may contribute to its effects on population health.